258 Agricultural injuries in Northern State (Haryana) of India: causal factors and magnitude. (20th November 2022) - Kumar, Adarsh; Dwivedi, Utkarsh
Abstract : Background: A large proportion of the workforce is engaged in agriculture. Farming involves working in adverse weather conditions, with traditional tools and modern equipment by all age groups. On Indian farms, about 263 million workers work and produce about 300 million tons of food grains from 157 million ha. Injuries on farms occur but go unreported because of a lack of surveillance. Aims: To assess the magnitude and causal factors of farm injuries Methods: Data was collected from the 47 grain market committees compensating agricultural injury victims in 13 districts of Haryana, a northern state of India. Results: A total of 2501 cases were recorded. Compensation distributed was about US 5 million. Out of all, 777(31%) were fatality and 1724(69%) disability injures (amputations). The distribution among gender was male 157 (63%) and female 923(37%). The causal factors were agricultural implement/tools (121), tractor (170), fodder cutter (1154), thresher (238), electrocution (283), chemical (122), snakebites (99), hand tools (13), burns (10) and others (291). The most common body parts injured were the right arm (1242), left arm (357), right leg (57), left leg (27) and fatalities (777). Conclusions: Fodder cutters are the most common machine associated with injuries Electrocution and pesticide intake are common causes of fatalities Upper extremities are the most frequently injured body part 61% fatalities occurred among women Incidence rates: 20 and fatality 9 cases/100, 000 workers/year Learning Outcomes: Safety and warning for commonly used farm machines like fodder cutters, threshers and electrically operated equipment Acquired disability due to Farm injuries needs to be addressed with assistive devices to make these farmworkers productive Awareness among farmworkers about safety and potential hazards specially with new high-powered farm machines.